Factors Affecting the Pattern of Health Service Receipt in Patients with Diabetes Mellitus at the Pangirkiran Health Center, Padang Lawas Utara Regency - Enta Marlina Harahap; Haslinah Ahmad; Anto J. Hadi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Diabetes Mellitus (DM) is a global health problem, with an increasing prevalence rate. In Padang Lawas Utara Regency, especially at the Pangirkiran Health Center, DM sufferers face various obstacles in receiving optimal health services. Objective: The study aims to analyze the factors that affect the pattern of receiving health services for people with diabetes mellitus. Methods: This type of quantitative research with a cross sectional study design was conducted at the Pangirkiran Health Center, Padang Lawas Utara Regency. The population and sample were all 136 patients with diabetes mellate with an exhaustive sampling technique. Data collection using a research questionnaire. The data was processed and analyzed using chi-square tests and logistic regression as well as the presentation of data with tables accompanied by explanations. Results: The results of the study prove that knowledge (p=0.007) and socio-cultural (p=0.008) have a significant effect on the pattern of receiving health services for people with diabetes mellitus. The most influential variable is Exp knowledge (B)=4.942. Conclusion: The conclusion was obtained that knowledge factors about diabetes mellitus and socio-culture play a significant role in determining the pattern of health service receipt. Therefore, it is important for the Pangirkiran Health Center to improve health education programs, improve access to services, and involve families in the process of managing diabetes mellitus. This research is expected to provide policy recommendations to improve the quality of health services for people with diabetes mellitus in the region.